Project “Transformation Processes in Oasis Settlements in Oman” Report on the survey campaign spring 2003 in Maqta‘ and Ibrā’ - Häser, Jutta (2003)
Keywords: Archéologie – Oman

Project “Transformation Processes in Oasis Settlements in Oman” Report on the survey campaign autumn 2003 in Ibrā’ and al-Hamrā’ - Häser, Jutta; Schreiber, Jürgen (2003)
Keywords: Archéologie – Oman

Le style épistolaire comme source de l’œuvre religieuse à Tunis et à Djerba - Cohen, Biniyamin Raphael (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

Arabisation, francisation et tradition juive à Djerba - Deshen, Shlomo (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

Les poèmes liturgiques des femmes de Djerba - Guez-Avigal, Miriam (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

Les sources de quelques traditions de Djerba - Ripeld, Meyer (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

L’ile de Djerba : Le lieu et la Légende: examen de récits populaires - Sarig, Yaakov (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

Kissé Rahamim » sur le Talmud du rabbin Rahamim Houri de Djerba - Arned, Aharon (2003)
Bar-Ilan University
Keywords: Judaïsme – Djerba

al-Buʿd al-Tārīkhī li-Shurūḥāt al-Manẓūmāt al-ʿAqadiyya: al-Daʿā’im li-Ibn al-Naḍr al-Ibāḍī Unmūdhajan - Salimi, Abdulrahman al- (2003)
FMC 13 p.

Tārīkh Ṣuḥuf Abī ‘l-Yaqẓān: Qirā’a Taḥlīliyya - Nāṣir, Muḥammad Ṣāliḥ (2003)
FMC
Keywords: Journalisme – Mzab

Tārīkh al-Jazā’ir min khilāl Ṣuḥuf al-Shaykh Abī ‘l-Yaqẓān - Ibn ʿUmar, al-Ḥājj Mūsà b. Bakīr (2003)
FMC
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab

Ahammiyyat Qirā’at Fikr al-Shaykh Abī ‘l-Yaqẓān - Būḥajjām, Muḥammad b. Qāsim Nāṣir (2003)
FMC

Ṣiḥāfat Abī ‘l-Yaqẓān fī ʿAyn al-Shaykh ʿAbd al-Raḥmān [b. ʿUmar Bakillī] - Bājū, Muṣṭafà b. Ṣāliḥ (2003)
FMC
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab

al-Shaykh Abū ‘l-Yaqẓān wa’l-Maṭbaʿa al-ʿArabiyya - Bāḥarīz, Ibrāhīm (2003)
FMC
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab

News from the West. Letters from Oman, 1798-1806 - Witkam, Jan Just (2003)
Published at the occasion of the visit to Leiden University Library by H.E. the Minister of Awqaf and Religious Affairs of the Sultanate of Oman, Shaikh Abdullah bin Mohammed bin Abdullah al Salimi on Friday 11 July 2003. Presentation of manuscripts Or. 2241-IV (11, 2-10) in the University Library Leiden. Letters of Sultans Sulṭān b. Aḥmad b. Saʿīd and Badr b. Sayf b. Aḥmad b. Saʿīd al-Būsaʿīdī to the Dutch Governor-General in Batavia (in present-day Indonesia).
FMC
Keywords: Relations – Oman – Pays-Bas

Wājib al-ʿInāya bi’l-Turāth: al-Shaykh Abū ‘l-Yaqẓān Namūdhajan - Wumūsà, Muḥammad ʿĪsà (2003)
FMC
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973)

Maḥaṭṭāt Fikriyya fī Ṣiḥāfat Abī ‘l-Yaqẓān - Zaghīna, Muḥammad (2003)
FMC
Keywords: Abū ‘l-Yaqẓān; Ibrāhim (1888-1973); Journalisme – Mzab

Leadership and scholarship in Oman's modern Ibadi renaissance - Hoffman, Valerie J. (2003)
Paper presented at the Middle East Studies Association of North America (MESA) annual meeting, Anchorage, Alaska, 9 Nov. 2003.
FMC: On Abū Nabhān Jāʿid b. Khamīs al-Kharūṣī, his son Nāṣir, Abū Muḥ. Saʿīd b. Khalfān al-Khalīlī al-Kharūṣī, (Abū Muslim Nāṣir b. Sālim al-Ruwāḥī, Ṣāliḥ b. ʿAlī al-Ḥārithī,) Abū Muḥ. ʿAbdl. b. Ḥumayyid al-Sālimī.